2014
DOI: 10.4239/wjd.v5.i2.160
|View full text |Cite
|
Sign up to set email alerts
|

Chromium does not belong in the diabetes treatment arsenal: Current evidence and future perspectives

Abstract: Chromium is considered to have positive effects on insulin sensitivity and is marketed as an adjunctive therapy for inducing glucose tolerance in cases of insulin resistance ("the glucose tolerance factor"). Case reports on patients who received prolonged parenteral nutrition indeed showed that the absence of trivalent chromium caused insulin resistance and diabetes. However, whether patients with type 2 diabetes can develop a clinically relevant chromium deficiency is unclear. This review summarizes the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“…In spite of controversies [3], chromium (Cr) supplementation has been studied as a co-adjuvant diabetes therapy, due to its role in glucose/insulin metabolism [4]. Chromium may enhance insulin sensitivity by activating intracellular signaling pathways involved in glucose transporter 4 (GLUT4) translocation, consequently increasing glucose and amino acids transport [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of controversies [3], chromium (Cr) supplementation has been studied as a co-adjuvant diabetes therapy, due to its role in glucose/insulin metabolism [4]. Chromium may enhance insulin sensitivity by activating intracellular signaling pathways involved in glucose transporter 4 (GLUT4) translocation, consequently increasing glucose and amino acids transport [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding chromium, it is converted to holochromodulin, which then attaches to insulin receptor to increase its own insulin binding efficiency. 44 It was predicted that biotin and Cr may synergize to create a more effective treatment for type 2 diabetes mellitus. 45 A small, open-label clinical trial demonstrated that twice daily administration of biotin and Cr in combination with a dietary education program significantly reduced HbA1c in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there are still contradictory results from the available meta-analyses on the value of CrP in reducing IR in diabetic, obese or IGT patients. 8,18,19,[23][24][25][26][27] For instance, a meta-analysis concluded that chromium effects were non-relevant after stratifying the studies according to methodological quality, sponsor involvement, and a Western versus non-Western study location! 24 The latter is not a valid justification for excluding a study from a meta-analysis, given that gene, lifestyle and population variation all have an impact on the prevalence of PCOS and IR in any population.…”
Section: Discussionmentioning
confidence: 99%
“…8,18,19,[23][24][25][26][27] For instance, a meta-analysis concluded that chromium effects were non-relevant after stratifying the studies according to methodological quality, sponsor involvement, and a Western versus non-Western study location! 24 The latter is not a valid justification for excluding a study from a meta-analysis, given that gene, lifestyle and population variation all have an impact on the prevalence of PCOS and IR in any population. 28,29 While previous meta-analyses failed to show a beneficial effect of chromium supplementation, 25,26 a more recent meta-analysis suggested favorable effects of chromium on blood sugar level in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%